Cover Image, Volume 51, Issue 5. (26th September 2018) - Lei, Xiaohua; Cao, Yujing; Zhang, Ying; Qian, Jingjing; Zhao, Qian; Liu, Fangwu; Zhang, Tao; Zhou, Jiaxi; Gu, Ying; Xia, Guoliang; Duan, Enkui
Abstract : The cover image, by Xiaohua Lei, is based on the Original Article Effect of microgravity on proliferation and differentiation of embryonic stem cells in an automated culturing system during the TZ‐1 space mission, DOI:10.1111/cpr.12466 .